The cervical bruit: Sound spectral analysis related to severity of carotid arterial disease - Tavel, Morton E. (Clin Cardiol, 2007)
Cervical bruits may signal the presence of high‐grade narrowing of arterial supply to the brain. Previous small studies have suggested that severe arterial stenosis may produce bruits that persist longer and contain a greater proportion of higher‐frequency sound spectral components. This study included 96 patients referred for duplex/Doppler testing after cervical bruits had been detected. With the use of a stethoscope equipped with wireless communication to an ordinary handheld computer, we recorded these bruits, analyzed peak sound frequencies and the durations of sound persistence > 200 Hz, and correlated them with Doppler velocities. Overall, the durations and peak frequencies within the bruits correlated significantly with the peak Doppler derived velocities, that is, severity of arterial obstruction. In the presence of high‐grade arterial stenosis (peak Doppler velocity > 200 cm/s), bruits regularly possessed either high peak frequencies or prolonged signal durations with a sensitivity approaching 90%. Bruits containing lower and nonsustained peak frequencies were uncommonly associated with severe arterial obstruction. Only well‐transmitted bruits with frequencies reaching 200 Hz could be analyzed satisfactorily. In conclusion, we confirm earlier observations that peak frequencies and duration of arterial bruits correlate significantly with severity of underlying arterial obstruction. Equipment used is inexpensive, convenient, and portable. This method provides an objective means for confirming and quantifying subjective auditory impressions of bruits gained at the bedside. It can provide assistance in selecting patients for further testing and as a means for serial follow‐up of individuals with known disease.